Pathogenicity of Paecilomyces fumosaroseus (Wise) Brown & Smith, Beauveria bassiana (Bals.) Vuill. and Metarhizium anisopliae (Metsch.) sorokin on the striped flea beetle Phyllotreta striolata F. (Coleoptera: Chrysomelidae) - Priyatno, Tri Puji; Ibrahim, Yusof (Universiti Putra Malaysia Press, 2004)
The ability of three species of entomopathogenic fungi, Paecilomyces fumosoroseus (Wise) Brown & Smith, Beauveria bassiana (Bals.) Vuill. and Metarhizium anisopliae (Metsch.) Sorokin to cause infection on the adults, eggs and larvae of the striped flea beetle Phyllotreta striolata F. was tested. Only one isolate of M. anisopliae and none of the B. bassiana and P. fumosoroseus caused adult mortality in excess of 50% at a concentration of 2 x 107 conidia mL1. One isolate of?, fumosoroseus (Pf), one B. bassiana (Wls) and two of M. anisopliae (MPs and Cy3) were pathogenic to the first instar larvae of P. striolata causing more than 50% mortality at a concentration of 2 x 106 conidia mL1. The rate of larval mortality increased with increase in conidia concentration. The respective estimated LT50 values for Pf, Wls, MPs and Cy3 for the larvae at 2 x 106 conidia mL1 were2.9, 3.5, 3.0 and 3.0 days. The two isolates of M. anisopliae were also highly pathogenic to the eggs causing significant inhibition of hatching, while B. bassiana and P. fumosoroseus were less pathogenic. Estimates of the median lethal concentration for Cy3 and MPs were 13.0 x 105 and 5.03 x 105 conidia mL1 respectively.